Educación, estética y régimen visual en la configuración del sistema educativo argentino. (2012)
In the configuration of the school practices we can recognize a series of clear-cut visual features that not only delimit a particular relation between seeing and knowing, but also grant certain privileges to the sense of sight above other sensitive perceptions. These features are part of the aestheti-cizing function of the Argentine educational system whose education of the senses was a concern that combined a regime of truth, related to knowledge, with the production of specific sensitivities in which truth, beauty and morality were part of the same operation.